2023
DOI: 10.3390/ma16072709
|View full text |Cite
|
Sign up to set email alerts
|

Design Strategy of Corrosion-Resistant Electrodes for Seawater Electrolysis

Abstract: Electrocatalytic water splitting for hydrogen (H2) production has attracted more and more attention in the context of energy shortages. The use of scarce pure water resources, such as electrolyte, not only increases the cost but also makes application difficult on a large scale. Compared to pure water electrolysis, seawater electrolysis is more competitive in terms of both resource acquisition and economic benefits; however, the complex ionic environment in seawater also brings great challenges to seawater ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 102 publications
(114 reference statements)
0
11
0
Order By: Relevance
“…In particular, the oxidation of chloride ions involves a two-eletron transfer, exhibiting faster kinetics, whereas the oxidation of water to oxygen gas involves a four-electron transfer and a high activation barrier, resulting in sluggish kinetics. , Therefore, the chloride oxidation is more favorble, as previously reported for seawater splitting . Furthermore, chloride ions can be oxidized to hypochlorous acid (HClO) or chlorine gas at acidic pH, as shown in eqs and , along with their corresponding standard oxidation potential. 2 Cl = Cl 2 + 2 normale ( + 1.36 V vs NHE ) 2 Cl + 2 normalH 2 normalO = 2 HClO + 2 normalH + + 2 normale ( + 1.07 V vs NHE ) …”
Section: Resultsmentioning
confidence: 81%
“…In particular, the oxidation of chloride ions involves a two-eletron transfer, exhibiting faster kinetics, whereas the oxidation of water to oxygen gas involves a four-electron transfer and a high activation barrier, resulting in sluggish kinetics. , Therefore, the chloride oxidation is more favorble, as previously reported for seawater splitting . Furthermore, chloride ions can be oxidized to hypochlorous acid (HClO) or chlorine gas at acidic pH, as shown in eqs and , along with their corresponding standard oxidation potential. 2 Cl = Cl 2 + 2 normale ( + 1.36 V vs NHE ) 2 Cl + 2 normalH 2 normalO = 2 HClO + 2 normalH + + 2 normale ( + 1.07 V vs NHE ) …”
Section: Resultsmentioning
confidence: 81%
“…) that are doped into existing highly active OER catalysts. 92 Extensive analysis in 23,82,91,[93][94][95][96] has shown that sulphide doping and phosphide doping (anionic dopants) are very promising approaches to enabling stable performance in the presence of Cl − . 4.4.1.2.1.…”
Section: Modication Techniquesmentioning
confidence: 99%
“…This section will investigate anionic (S 2− and P 3− ) and polyanionic dopants (SO 4 2− and PO 4 3− ) that are doped into existing highly active OER catalysts. 92 Extensive analysis in 23,82,91,93–96 has shown that sulphide doping and phosphide doping (anionic dopants) are very promising approaches to enabling stable performance in the presence of Cl − .…”
Section: Different Oer Catalystsmentioning
confidence: 99%
“…[13][14][15] Direct seawater electrolysis is often carried out in alkaline media to suppress CER. [16][17][18] One additional concern related to the potential challenges associated with direct seawater electrolysis is the chemical stability of the anion exchange membranes (AEM). [19] Also, the presence of contaminants and corrosive ions in seawater can lead to corrosion of the electrodes, bipolar and end flow plates, and membranes over extended periods of operation.…”
Section: Introductionmentioning
confidence: 99%